A new simple h-mesh adaptation algorithm for standard Smagorinsky LES: a first step of Taylor scale as a refinement variable - S Kaennakham (International Journal of Multiphysics, 2016)
The interaction between discretization error and modeling error has led to some doubts in adopting Solution Adaptive Grid (SAG) strategies with LES. Existing SAG approaches contain undesired aspects making the use of one complicated and less convenient to apply to real engineering applications. In this work, a new refinement algorithm is proposed aiming to enhance the efficiency of SAG methodology in terms of simplicity in defining, less user's judgment, designed especially for standard Smagorinsky LES and computational affordability. The construction of a new refinement variable as a function of the Taylor scale, corresponding to the kinetic energy balance requirement of the Smagorinsky SGS model is presented. The numerical study has been tested out with a turbulent plane jet in two dimensions. It is found that the result quality can be effectively improved as well as a significant reduction in CPU time compared to fixed grid cases.